Evaluation of International Class Program Through CIPP Model: Case in Bachelor of Sharia Economics Study Program, UIN Sunan Ampel Surabaya - Wigati, Sri; Hasan, Nurul Fatma (Al-Buhuts, 2023)
International Class Program (ICP) of Bachelor of Sharia Economics (BSE) in UIN Sunan Ampel Surabaya was initiated to create excellent graduates who are able to compete in international competition. This study aimed to evaluate International Class Program (ICP) of Bachelor of Sharia Economics (BSE) in UIN Sunan Ampel Surabaya. The evaluation on International Class Program has been done through CIPP model; that is Context, Input, Process, and Product. The object being focused in this research were an International Class Program (ICP) of Bachelor of Sharia Economics (BSE) UIN Sunan Ampel Surabaya, which consists of 24 students and 15 lecturers. Context dimension evaluates learning objectives; the result is very good (acknowledged by the independent accreditation agency LAMEMBA). Input dimensions evaluates lecturers, students, curriculum, and facilities & infrastructures; the results are qualified for lecturers and students, very good for curriculum, and good for facilities & infrastructures. Process dimension evaluates pedagogy and professional; the result is very good. Product dimension evaluates academic and nonacademic achievements; the result is good. By employing these evaluations, policymakers and all the elements involved can conduct for evaluations to develop and to strengthen existing ICP programs